2019
DOI: 10.1007/s40093-019-00308-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different initial C/N ratio of cow manure and straw on microbial quality of compost

Abstract: Purpose The effect of different initial carbon to nitrogen (C/N) ratios on the prevalence of Salmonella spp., fecal coliforms and helminth eggs over composts produced from several mixtures of maize straw (S) and dairy manure (M) was investigated. Methods Four C/N ratios (21, 22, 27, and 38) were evaluated, including one with manure only (C/N 21). The composting process was performed under field conditions in northern Mexico. Results The process lasted 51 days; Salmonella spp. was reduced 1-2 log (> 94%) in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The lower compost temperature was recorded in T5 (26.4 ± 1.0 °C). Similarly, a research reported that temperature fluctuation in the compost pile overtime related to consumption of organics by microorganisms [ 30 ]. In general, in all treatments an increase in temperature was observed at the early weeks (2–4 weeks) and a temperature decline at later weeks (5–10 weeks) of the composting period.…”
Section: Resultsmentioning
confidence: 99%
“…The lower compost temperature was recorded in T5 (26.4 ± 1.0 °C). Similarly, a research reported that temperature fluctuation in the compost pile overtime related to consumption of organics by microorganisms [ 30 ]. In general, in all treatments an increase in temperature was observed at the early weeks (2–4 weeks) and a temperature decline at later weeks (5–10 weeks) of the composting period.…”
Section: Resultsmentioning
confidence: 99%
“…The C/N and the water content of the composting mixture were about 30:1 and 60%, according to the research studies and our laboratory compost results ( Sánchez et al, 2017 ; Macias-Corral et al, 2019 ). Here, 1.592 tons of cow dung, 2.556 tons of grounded straw, and 1.852 tons of water were mixed.…”
Section: Methodsmentioning
confidence: 55%
“…In composting environments, it will take a long time to obtain the same results. It took about 4 days to inactivate Salmonella when the composting temperature was higher than 55°C [Marilyn et al, 2009; Macias-corral et al, 2019 ]. E. coli could be eliminated in 25 days when the composting temperature was between 45 and 55°C ( Wichuk and McCartney, 2007 ; Macias-corral et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the fourth week, through physical observation, ground lice and worms were found. [23] stated the application of organic fertilizer containing blood meal facilitates the development of earthworms. At the end of the composting period, the mixture of ingredients has dark colored and smelly soil.…”
Section: C/n Ratio Of Fertilizer By Bioactivating Blood Meal Of Slaugmentioning
confidence: 99%